(untitled) (Herald of Journalism, 2026)
The article examines the specific features of creating creolized texts in online media as the object of research and the mechanisms of content encoding on Instagram as the subject of analysis. The study aims to identify and define the codes and encoding strategies used to convey information on this social network, as well as to determine the degree of creolization in the positioning of popular Kazakhstani online media outlets, including regional ones. The research process included the examination of mechanisms for developing news accounts, de-signing covers and avatars, structuring posts and profile sections, and analyzing content encoding strate-gies. Particular attention is paid to the diversity of encoding options employed in creolized texts within Kazakhstani news accounts on Instagram, explored through content analysis and polycode discourse analysis. The applied formats and their combinations are considered with regard to the platform’s techni-cal affordances and social mechanisms. The scientific significance lies in the proposed systematization of approaches to studying the process of creolization in media texts on social networks. The practical significance is reflected in the potential application of the findings to enhance content management effectiveness. The study demonstrates the predominance of visual-verbal codes in Kazakhstani online media on Instagram and identifies patterns in the use of structural elements and their functional roles. The article also addresses the issue of terminological unification in the study of mixed texts and sub-stantiates the use of the terms creolized text, code, and polycode. Special emphasis is placed on the use of the “carousel” technique in encoding media texts, leading to the conclusion that this format increases the complexity of encoding mechanisms. By expanding the understanding of interaction between verbal and visual components, the authors propose analytical tools for examining and optimizing digital con-tent, relevant for both scholars and practitioners in media communications.